How do information sources influence the reported Cerebral Performance Category (CPC) for in-hospital cardiac arrest survivors? An observational study from the UK National Cardiac Arrest Audit (NCAA). (August 2019) - Reynolds, Emily C.; Zenasni, Zohra; Harrison, David A.; Rowan, Kathryn M.; Nolan, Jerry P.; Soar, Jasmeet; ,
Abstract: Aim: Cerebral Performance Category (CPC) can be used to categorise neurological outcome after cardiac arrest. There is no consensus on what information sources can be used to derive the CPC. This study describes the information sources used by hospitals participating in the UK National Cardiac Arrest Audit (NCAA) and their impact on the CPC reported for individuals surviving an in-hospital cardiac arrest (IHCA). Methods: Data on the CPCs and on the information source used to assess the CPC (either case note review, communication with clinical team or direct patient assessment) were abstracted for individual adult patients who survived to discharge following an IHCA in an acute hospital participating in NCAA between 1 May 2014 and 30 April 2016. Results: Data for 33, 114 IHCAs (in 31, 783 patients) from 195 hospitals were reported to NCAA, of whom 6093 (18.4%) survived to hospital discharge. Of these hospital survivors, 5492 (90.1%) had both the CPC and information source reported: case note review (3989 patients, 72.6%), communication with the clinical team (1053 patients, 19.2%); and direct patient assessment (450 patients, 8.2%). Most (96.6%) survivors were reported to have had a good neurological outcome (CPC 1 or 2). There were small differences in the CPC reported derived from the different information sources but these differences were not clinically important. Conclusion: In the UK IHCA audit, the most commonly used information source for CPC assessment is case notes. Most survivors of IHCA are reported as having a CPC score of 1 or a good outcome (CPC scores 1 or 2).